PENGARUH KERUSAKAN SPAREPART TERHADAP POWER PANCAR RADIO VHF A/G PORTABLE ADC DI PERUM LPPNPI AIRNAV CABANG PALEMBANG - Wimatra, Ayub; Caesar Akbar, Muhammad; Sulistyo, Bayu (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2023)
In the world of aviation, the tool used for communication between aircraft in the air with ATC (Air Traffic Controller) officers on the ground is VHF Air to Ground radio. This radio has a very vital role in the world of aviation therefore this tool must be able to function properly. Many aspects can affect damage to the VHF A/G radio and cause the transmitting power emitted by the radio to not allow pilots and air traffic controllers to communicate. Among others is the damage of spare parts on the VHF A/G radio that occurs at Perum LPPNPI Airnav Palembang Branch. This research is qualitative research. Data collection techniques using interviews, observation, and documentation. The results of the study prove that damage to spare parts on the VHF A/G radio can affect the transmitting power and cause communication between pilots and ATC officers at Sultan Mahmud Badaruddin II airport.